Kajian Psikologis terhadap Pengaruh Pandangan Islam dalam Pembentukan Sikap dan Perilaku LGBT : Studi Kasus Pesta Seks 56 Gay di Jakarta Selatan - Nurhafidah, Leni; Nurfalah, Fadilah; Abdillah, Mochamad Ilham; Prabawa, Salvia Nasywa; Fajrussalam, Hisny (Jurnal Keislaman, 2025)
The LGBT (Lesbian, Gay, Bisexual, and Transgender) phenomenon has become a controversial global issue, including in Indonesia, where social and religious norms play a major role in shaping people's attitudes. Within the Islamic context, the LGBT community is regarded as being in opposition to human nature and the tenets of sharia law, leading to its frequent rejection. From a psychological perspective, individuals who identify as LGBT face mental distress, anxiety, and identity conflict due to social stigma. This research aims to analyze the influence of Islamic views in shaping attitudes towards LGBT and to examine the psychological impact of social marginalization, with a case study of the "56 Gay Sex Party" in South Jakarta. The research employed a qualitative approach, incorporating a literature review, social media analysis, and a Likert scale survey of religious leaders and the general public. The results indicated that 83.3% of respondents exhibited a negative stance towards LGBT individuals, with religion being the predominant factor influencing their attitudes. Moreover, a significant proportion of religious leaders, 85.7%, firmly asserted the pivotal role of Islamic teachings in shaping attitudes toward LGBT individuals. From a psychological standpoint, individuals who identify as LGBT frequently encounter identity conflict and emotional distress, which, in some cases, is influenced by factors such as parenting, trauma, or emotional escapism. Furthermore, 66.7% of respondents expressed the opinion that the LGBT community is growing, particularly through the medium of social media, which has emerged as a platform for advocacy and debate.